Tanggap Tanaman Jagung terhadap Aplikasi POC Urin Sapi dan Pupuk Anorganik di Lahan Pasang Surut Tipe Luapan C - Ruli Joko Purwanto; Karlin Agustina; Yursida Yursida (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
The research was conducted in the village of Banyu Urip at Banyuasin district from March to June 2013. This study aimed to examine the effect of organic manure of fermented cow urine (liquid organic fertilizer/ POC) and combined with different doses of inorganic fertilizer on the growth and yield of corn land in the tidal area overflow type C. This study uses a randomized block design consisting of 5 treatment was repeated 5 times. Each treatment unit with a plot size of 1.5 m x 10 m. Treatment in this study are as follows: J0 = 100% recommended dose of inorganic fertilizer without POC cow urine; J1 = 75% recommended dose of inorganic fertilizer + POC cow urine; J2 = 50% recommended dose of inorganic fertilizer + POC cow urine; J3 = 25% recommended dose of inorganic fertilizer + POC cow urine, and J4 = 100 % POC cow urine without inorganic fertilizers. The results of fertilizer application treatments using organic and inorganic fertilizers on maize showed significant effect on all observed variables. Further test results show that the inorganic fertilizer treatment J2 = 50% of the recommended dose of cow urine + POC gives the highest yield for plant height (162.22 cm), number of leaves, corn with cornhusk weight (187.70 g), the weight of the corn without cornhusk (177.54 g), dry shelled weight (139.05 g), weight of 100 grains (30.87 g) and the number of seed rows per ear (16.60), as well as significantly different to the other treatments.